1989
DOI: 10.1115/1.3262271
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Modeling of the Gas Turbine Blade Transition Process as Disturbed by Wakes

Abstract: Heat transfer measurements have been made on a transonic turbine blade undergoing natural transition and with a simulation of the effect of NGV wake interactions. The use of wide bandwidth heat transfer instrumentation permits the tracking of individual unsteady events that were identified as being due to either the impinging wakes or to the turbulent spots occurring within the transition process. Trajectories of these events as seen by the blade surface instrumentation have been measured. Numerical models hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
2
19
1
Order By: Relevance
“…The results of LaGraff et al [16] and Doorly et al [15] referred to above employed Wake Effect \ Spots Fig. 1.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The results of LaGraff et al [16] and Doorly et al [15] referred to above employed Wake Effect \ Spots Fig. 1.…”
Section: Introductionmentioning
confidence: 84%
“…These investigations established the usefulness of such non-intrusive sensors for the examination of intermittent flows. Following this work, Doorly et al [15] and LaGraff et al [16], studied the end-stage of the transition process on a gas-turbine blade in a two-dimensional cascade. Typical results of the work of LaGraff et al [16] are found in Figure 1, which is an illustration of the unsteady character of transition in a wake-disturbed environment.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…ory of turbulent spots which accounts for wake induced and natural transition and shows excellent agreement with the experimental results. Other approaches to solve the problem have been proposed by Doorly (1987), LaGraff et al (1988 or interpreting the results of time resolved measurements obtained by means of high frequency response sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of moving shocks generated by the bars have also been studied and again many interesting phenomena revealed [34,35]. The ability to identify turbulent and laminar boundary layers has led to further studies of transition on turbine blades [13,36]. Transition detection using heated thin films has long been an established technique and also employed by the Oxford group [37].…”
Section: The Isentropic Light Piston Tunnel (Ilpt) and Cascade Studiesmentioning
confidence: 99%